Endocrine therapy for cancer. Issue 4 (April 2021) - Elder, Kenneth; Michael Dixon, J.; Blackmur, James P.; Laurie, Jacqueline
Abstract: Endocrine therapy is widely used to treat cancers whose growth is dependent on hormonal stimulation, most commonly breast, prostate and endometrial cancers. The principles behind its use, indications, different medications available and some of the evidence to support its use are described. Endocrine therapies avoid the toxicities associated with chemotherapy, but do have recognized side effects that can impact on quality of life.